2022
DOI: 10.2147/copd.s341484
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm Ultrasound is an Imaging Biomarker that Distinguishes Exacerbation Status from Stable Chronic Obstructive Pulmonary Disease

Abstract: Background: Evaluating the diaphragm muscle in chronic obstructive pulmonary disease (COPD) is important. However, the role of diaphragm ultrasound (DUS) in distinguishing the exacerbation status of COPD (AECOPD) is not fully understood. We set this study to evaluate the role of DUS as a biomarker for distinguishing the AECOPD. Methods: COPD patients who underwent DUS were enrolled between March 2020 and November 2020. The diaphragm thickening fraction (TF max ) and diaphragm excursion (DE max ) during maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In COPD assessment, thoracic ultrasound offers valuable information on lung hyperinflation, diaphragmatic excursion, and disease severity, assisting in treatment decisions, and therapy monitoring. [85][86][87] POCUS is strongly supported by evidence for assessing hernia, cholecystitis, and diverticulitis. Its integration into clinical practice improves patient care through timely and accurate diagnoses, leading to better outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…In COPD assessment, thoracic ultrasound offers valuable information on lung hyperinflation, diaphragmatic excursion, and disease severity, assisting in treatment decisions, and therapy monitoring. [85][86][87] POCUS is strongly supported by evidence for assessing hernia, cholecystitis, and diverticulitis. Its integration into clinical practice improves patient care through timely and accurate diagnoses, leading to better outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…A further study showed that DD has high specificity and sensitivity in predicting NIV failure in AECOPD patients and may help identify patients who need NIV therapy and be helpful in predicting the duration of hospitalization [ 58 ]. A recent study explored the value of diaphragm markers for distinguishing AECOPD from stable COPD [ 18 ], which is a step forward in the role of the diaphragm between AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…During severe AECOPD, progressive development of dynamic hyperinflation causes a change in the geometry of the chest wall and diaphragm, with impaired lung function [ 16 , 17 ]. Another study confirmed that lower diaphragm thickening fraction (DTF max ) and diaphragm excursion (DE max ) during maximal deep breathing were associated with AECOPD, which leads to the possibility of an imaging biomarker distinguishing AECOPD from stable status [ 18 ]. The impairment of diaphragmatic function may be one of the main pathophysiological mechanisms in COPD that seems related to acute exacerbation [ 19 ] .…”
Section: Introductionmentioning
confidence: 98%
“…3 ). Similar to the measurement method of An [ 22 ], the diaphragm excursion (DE) and diaphragm thickening fraction (TF) were measured at tidal inspiration and at maximal deep inspiration. Pulmonary function tests were performed in accordance with the standards of the European Respiratory Society [ 23 ], and the FEV 1 , forced vital capacity (FVC), FEV 1 /FVC, inspiratory capacity (IC), functional residual capacity (FRC), residual volume (RV), total lung capacity (TLC) and RV/TLC were recorded.…”
Section: Methodsmentioning
confidence: 99%